(untitled) (ENTHYMEMA, 2023)
We present Macchine per leggere project, a collaboration between the Department of Literary, Philosophical and Art History Studies of the university of Rome “Tor Vergata” and the MiC Center for Books and Reading. The project aims at creating a digital environment (desktop and mobile) that introduces secondary school students to the knowledge and use of computational text analysis as a cue for approaching the reading of classics of Italian literature (among others that will be made available on the site, Il piacere, I Malavoglia, Il fu Mattia Pascal...). The distant reading approach and a set of computer tools for corpus analysis and text mining (word cloud, term and syntagma frequency indices, topic modeling, sentiment, and network analysis), combined with other resources such as geolocation on digital maps of literary places, will be presented both as a method for simulating reading strategies in a virtual environment and as models for integrating traditional hermeneutic practices-close reading. In a dedicated section of the site, the various tools will be available to students in the form of a web application so that they can experiment independently and on other texts in their possession with the distant approach proposed as part of the project.